Hydrophobic ZnO-TiO2 Nanocomposite with Photocatalytic Promoting Self-Cleaning Surface. (4th October 2015) - Wei, Qiang; Wang, Shaodan; Li, Wei; Yuan, Xiaoxue; Bai, Yu
Abstract : The hydrophobicity and self-cleaning are the important influence factors on the precision and environment resistance of quartz crystal microbalance (QCM) in detecting organic gas molecules. In this paper, ZnO nanorod array is prepared via the in situ method on the QCM coated with Au film via hydrothermal process. ZnO nanorod array film on QCM is modified by β -CD in hydrothermal process and then decorated by TiO2 after being impregnated in P25 suspension. The results show that as-prepared ZnO-TiO2 nanocomposite exhibits excellent hydrophobicity for water molecules and superior self-cleaning property for organic molecules under UV irradiation.